2020
DOI: 10.7759/cureus.10378
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin: A Closer Look at a Potential Remedy

Abstract: Amid the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, the search for effective treatment and vaccines has been exponentially on the rise. Finding effective treatment has been the core of attention of many scientific reports and antivirals are in the center of those treatments. Numerous antivirals are being studied for the management of the coronavirus disease 2019 (COVID-19) pneumonia caused by the SARS-CoV-2. Remdesivir was the first drug to gain emergency FDA approval to be used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Ivermectin is an anthelmintic agent with known efficacy against some single strain RNA viruses, e.g., HIV-1 and dengue virus. Ivermectin can significantly reduce SARS-CoV-2 in-vitro replication by inhibiting the shuttle protein responsible for nucleocytoplasmic transport of the virus [ 60 62 ]. Oral ivermectin has been shown to cause lower mortality in COVID-19 patients [ 60 ], but effective plasma concentrations are not achievable with safe oral doses.…”
Section: Inhibiting Nuclear Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Ivermectin is an anthelmintic agent with known efficacy against some single strain RNA viruses, e.g., HIV-1 and dengue virus. Ivermectin can significantly reduce SARS-CoV-2 in-vitro replication by inhibiting the shuttle protein responsible for nucleocytoplasmic transport of the virus [ 60 62 ]. Oral ivermectin has been shown to cause lower mortality in COVID-19 patients [ 60 ], but effective plasma concentrations are not achievable with safe oral doses.…”
Section: Inhibiting Nuclear Transportmentioning
confidence: 99%
“…Ivermectin can significantly reduce SARS-CoV-2 in-vitro replication by inhibiting the shuttle protein responsible for nucleocytoplasmic transport of the virus [ 60 62 ]. Oral ivermectin has been shown to cause lower mortality in COVID-19 patients [ 60 ], but effective plasma concentrations are not achievable with safe oral doses. Meanwhile, due to the potential benefits of ivermectin in hospital mortality, it is extensively used in COVID-19 treatment or prevention regimens and there are different registered clinical trials which have tested oral, parenteral, and nasal ivermectin alone or in combination with other medications.…”
Section: Inhibiting Nuclear Transportmentioning
confidence: 99%
“…It was shown that the short term and high dosage hydroxychloroquine failed to provide protection or treatmet against SARS-CoV-2, after 4 days of exposure [43] . Inhalant form of IVM has also been re-purposed as more economical and efficient way to curtail the SARS-CoV-2 infection [44] . At this point of rapidfire ideas and lab scale research, it is required to extract clinically relevant data regarding the promise of IVM against COVID-19.…”
Section: Ivermectin and Covid-19mentioning
confidence: 99%